Behavior of FRP-RC Columns Using BFRP Ties under Concentric Loading - Obeidat, Khaled (2019)
A Master of Science thesis in Civil Engineering by Khaled Obeidat entitled, “Behavior of FRP-RC Columns Using BFRP Ties under Concentric Loading”, submitted in December 2019. Thesis advisor is Dr. Farid Abed. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).